Fiber-level numerical simulation of biaxial braids for mesoscopic morphology prediction validated by X-ray computed tomography scan. (1st August 2021) - Ghaedsharaf, Mohammad; Brunel, Jean-Evrard; Lebel, Louis Laberge
Abstract: This paper proposes a modeling methodology to predict the 3D and internal geometry of biaxial braids. Inspired by the digital element approach, braided yarns are modeled as a bundle of virtual fibers. Here we adopt truss elements to a virtual fiber with actual material properties instead of beam elements that have limitations due to the beam flexural rigidity. The mesoscopic morphology prediction of two common braid patterns of the diamond (1/1) and regular (2/2) are validated by a comprehensive quantitative comparison with X-ray micro-computed tomography (CT) scans of braided carbon fibers. We find that the fiber-level frictional behavior is able to explain the jammed state of braids wherein the frictional dissipation energy quickly grows, while the braid has a stable elongation, diameter, and braid angle. Parametric studies illustrate how the increase in the coefficient of friction affects the yarn cross-sectional shape, whereas it has an insignificant effect on the crimp and jammed state of braids. Models also reveal that changing a wide range of the fiber modulus of elasticity hardly impacts the mesoscopic morphology and crimp of the braids. Graphical abstract: Image 1 Highlights: Fiber-level modeling methodology is proposed to predict the mesoscopic morphology of 1/1 and 2/2 biaxial braids. Braid diameter and yarn cross-section area are predicted with an average accuracy over 98%. Varying the fiber-to-fiber coefficient of friction has negligible impact on the braid jammed state angle. Low fiber-to-fiber coefficient of friction produces lenticular shaped yarn, while a high one produces an oval shaped yarn. Increasing the fibers' Young modulus neither impacts jammed state nor the yarn shape.